ANALISIS KELAYAKAN TURBIN ANGIN KECEPATAN RENDAH TIPE NT1000W DI WILAYAH TERPENCIL - Redaksi Tim Jurnal (Energi & Kelistrikan, 2018)
This research discusses the fulfillment of the electricity needs of remote communities that are closely related to electrification ratios. Electrification ratios in some isolated areas and scattered islands in Indonesia are still very low. To date, most of the electricity needs in Indonesia is still supplied by Diesel Power Electricity Generator (PLTD) which uses diesel as its fuel. Therefore, it is necessary the utilization of renewable energy as one step to fulfill the electrical energy needs. This research studies about the utilization of wind energy with PLTB by using low speed wind turbine to fulfill the electricity needs of remote communities and scattered islands in Indonesia. NT1000W is the latest technology of low speed wind turbine that can operate at wind speed of 1 m/d up to 60 m/d appropriate to the wind conditions in Indonesia. Testing conducted in west Sumatera particularly in Padang city and Kapo-Kapo Island provide a feasibility of PLTB NT1000W technically and financially.